Photopolymerization and photophysical properties of amine linked benzophenone photoinitiator for free radical polymerization - Temel, Gokhan; Enginol, Burak; Aydin, Meral; Balta, Demet Karaca; Arsu, Nergis (ELSEVIER SCIENCE SA, 2011)
Synthesis of amine linked type II photoinitiator (BPDEA) was achieved in high yields and photopolymerization of mono and multiacrylate monomers was performed with this photoinitiator in the absence of a coinitiator. BPDEA is more effective than benzophenone (BP) with the coinitiator (MDEA) system under inert atmosphere in photoinduced free radical polymerization of acrylates. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Benzophenone; Free radical polymerization; Type II system; UV curing; COINITIATOR AMINE; PHOTOCHEMISTRY; INITIATORS; ACID; Chemistry